Evaluation of Flexographic Printing Technology for Multi-busbar Solar Cells. (April 2015) - Lorenz, A.; Senne, A.; Rohde, J.; Kroh, S.; Wittenberg, M.; Krüger, K.; Clement, F.; Biro, D.
Abstract: Rotational flexographic printing is a promising high-throughput technology for the front side metallization of silicon solar cells. Very low silver consumption and the possibility to realize narrow contact fingers make this technology particularly interesting for multi-busbar solar cells. Within this work, fundamental printing tests have been carried out on a flexographic roll-to-flat machine using an experimental anilox roll and elastomeric laser-engraved printing plates. A double printing process with intermediate drying step has been applied. Contact fingers down to 33 μm in width and up to 8 μm in height have been realized using this technology. Lateral resistances in the range 500 to 1500 Ω/m have been determined by four point measurement method. These results underline the capability of flexographic printing for fine line metallization of multi-busbar solar cells.